Socialization Of Healthy Snacks As An Efforts To Increase Nutrition In Indonesia-Malaysia Border Elementary School Students - Eti Sunarsih; Emi Sulistri; Citra Utami; Nurul Husna; Andi Mursidi; Dian Mayasari (International Journal of Public Devotion, 2022)
Along with the times, food has also experienced a significant development. Starting from a variety of processed foods, which can be served in various new forms and variations. During the growth period, children usually prefer snacks as snacks compared to eating healthy foods such as vegetables and fruits. Snacks that are developing today contain more colorful foods and contain harmful substances. The purpose of this socialization is so that children pay more attention to the snacks they consume. The method used is the first survey, the second choosing the location of service, the third collection of materials/materials, the fourth preparation of the material, the fifth meeting with the school wedding, the sixth implementation of the activity, the seventh documentation and the eighth activity reporting. The results obtained are that the implementation of the service carried out in Gersik Village, Jagoi Babang District, Bengkayang Regency went well and ran smoothly, which can be seen from the enthusiasm of the children when participating in the activities and indications that students have experienced an increased understanding of healthy snacks.